Parallel experimental study of a novel super-thin thermal absorber based photovoltaic/thermal (PV/T) system against conventional photovoltaic (PV) system - Peng Xu; Xingxing Zhang; Jingchun Shen; Xudong Zhao; Wei He; Deying Li (Energy Reports, 2015)
Photovoltaic (PV) semiconductor degrades in performance due to temperature rise. A super thin-conductive thermal absorber is therefore developed to regulate the PV working temperature by retrofitting the existing PV panel into the photovoltaic/thermal (PV/T) panel. This article presented the parallel comparative investigation of the two different systems through both laboratory and field experiments. The laboratory evaluation consisted of one PV panel and one PV/T panel respectively while the overall field system involved 15 stand-alone PV panels and 15 retrofitted PV/T panels. The laboratory testing results demonstrated the PV/T panel could achieve the electrical efficiency of about 16.8% (relatively 5% improvement comparing with the stand-alone PV panel), and yield an extra amount of heat with thermal efficiency of nearly 65%. The field testing results indicated that the hybrid PV/T panel could enhance the electrical return of PV panels by nearly 3.5%, and increase the overall energy output by nearly 324.3%. Further opportunities and challenges were then discussed from aspects of different PV/T stakeholders to accelerate the development. It is expected that such technology could become a significant solution to yield more electricity, offset heating load freely and reduce carbon footprint in contemporary energy environment.
Keywords: 330